Monitoring Design on PV and Battery PLTS for Power Regulation on Water Pump - Sukamta, Sri -; Arief, Ulfah Mediaty (Universitas Nurul Jadid, 2025)
The increasing use of solar energy as a source of electrical energy encourages the use of remote monitoring systems to determine the performance of solar panels. The purpose of this study is to conduct a monitoring system for solar panel (PV) and battery output for water pump loads. The method used is to design a monitoring system using the microcontroller NodeMCU ESP8266 and sensor INA219. The first step is to determine the capacity of the PV, battery, and water pump. Then do microcontroller programming and field testing. The INA219 sensor measures the operating voltage and current in real time, the voltage, power, and current of the PV connected to the circuit. Experimental investigations that have been carried out to verify the effectiveness of the proposed monitoring system have shown that proper examination of the collected data allows the monitoring system to be enlarged. The monitoring system is able to perform measurements well for 3 months. The results of monitoring measurements in this study are also influenced by the intensity of solar radiation.